Musical performance as discourse An analysis proposal - Oliveira Lemos, Caio Victor de [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2019)
This article investigates the possibility of apprehending the effects of meaning in musical speech from a discursive perspective. We firstly present some principles of the theory of enunciation, followed by the analysis of two musical videos - seen as syncretic objects, which assemble music, gesture, and other sounds and visual elements. The videos present two performances of Benjamin Britten's Nocturnal op.70 played by different performers - Paul Galbraith and Kazuhito Yamashita. Thus, through the marks left by the enunciation subject on the videos, we will be able to infer how the construction of meaning was brought about, which discursive strategies were used, and therefore show that different images were created by each enunciator, revealing the operational and analytical gain of the tools proposed for the musical performance.
Keywords: Musical performance; Musical discourse; Enunciative categories; Syncretic object